Fluocinolone acetonide intravitreal implant for the treatment of diabetic macular edema - Messenger WB; Beardsley RM; Flaxel CJ (Dove Medical Press, 2013)
Wyatt B Messenger, Robert M Beardsle, Christina J FlaxelCasey Eye Institute, Oregon Health and Science University, Portland, OR, USAAbstract: Diabetic macular edema (DME) remains one of the leading causes of moderate to severe vision loss. Although laser photocoagulation was the standard of care for several years, few patients achieved significant improvements in visual acuity. As a result, several pharmacotherapies and surgeries have been investigated. The fluocinolone acetonide devices are one of the latest therapies considered for the treatment of DME. Despite bringing significant improvements in visual acuity, fluocinolone devices are associated with cataract formation, increased intraocular pressure (IOP), and surgery to lower IOP. Due to the risk of complications, fluocinolone acetonide devices should be considered only in cases refractive to first-line therapies. In this review, we evaluate current and emerging therapies for DME, with special emphasis on fluocinolone acetonide intravitreal devices.Keywords: diabetic macular edema, fluocinolone, anti-VEGF, triamcinolone, dexamethasone